Pedagogical Principles and Ethical Values in the Codification of the Qur'an: A Historical-Phenomenological Analysis - Mokhamad Miptakhul Ulum; Dedi Djubaedi; Cecep Sumarna (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
The history of the codification of the Qur'an has been extensively documented, but existing research often focuses on philological and political narratives, leaving a significant gap in research on the educational philosophy underlying the process. This type of research is qualitative. This study investigates the educational values contained in the transition from oral revelation to written codex through a historical-phenomenological approach. The historical approach is used to analyze the stages of codification from the era of the Prophet Muhammad to the Mus'haf Uthman, not merely as administrative events, but as a deliberate pedagogical framework for the preservation and standardization of knowledge. The phenomenological approach is used to analyze various theories related to the socio-cultural context of the Qur'an. This study finds that the codification process institutionalized core educational values, including itqan (accuracy), amanah (intellectual integrity), and the democratization of literacy. The uniqueness of this study lies in its reinterpretation of historical documents as a structured pedagogical movement. These findings contribute to the field of Islamic Education by providing historical precedents for modern curriculum standardization and quality assurance in religious education.